Development of a kit-like radiofluorinated biomolecule leading to a controlled self-assembly of 18F nanoparticles for a smart PET imaging applicationElectronic supplementary information (ESI) available: Syntheses and characterization of 1-Cold; disulfide reduction and cyclization, biocompatibility, stability, radiolabeling, cell uptake, PET imaging with inhibitor and biodistribution of probe 1. See DOI: 10.1039/c7cc03040a - Lin, Jianguo; Wang, Wei; Li, Ke; Huang, Hongbo; Lv, Gaochao; Peng, Ying; Luo, Shineng; Qiu, Ling (2017)
A kit-like 18 F-fluorination method has been successfully applied to prepare an activatable probe 1 with good radiochemical yield and high specific activity. The probe has good in vitro stability and favorable cell membrane permeability. A controlled condensation reaction was initiated, and self-assembly into nanoparticles occurred when the probe was in a reducing environment. Positron emission tomography (PET) imaging of the biothiol level in living subjects was conveniently and precisely realized using this probe. The present study may provide a new platform for the development of "smart" PET tracers for tumor imaging. A kit-like radiofluorinated biomolecule was designed for convenient and precise PET imaging of biothiol levels in living subjects.